Facilidades y Seguridad Turística en la Comunidad La Moya, cantón Riobamba. - Sacta Cabezas, Janeth Estefanía (2023)
The community La Moya is a tourist place that offers several activities to its visitors, with beautiful landscapes that tourists should observe beautiful landscapes, in addition to acquiring the products made by the people of that community. For the place, tourist facilities are essential because they ensure the tourist’s stay. The present research aims to determine if tourist facilities contribute to tourism security in the community of La Moya of the Riobamba cantón. The methodology used in this work is as follows: the type of research is a documentary and field research, the technique used is the observation where notes were taken to help the study, and then with that information perform, surveys of both variables. The surveys were applied and then the IBM program was used to tabulate the information obtained from them and get the results which gave greater importance to the information points, the creation of visitor reception centers, trails, shade, and rest stations, camping areas, viewpoints, sanitary batteries, and parking areas, in addition, it was determined that the tourist facilities contribute to tourist security in the community of La Moya of the Riobamba canton. Afterward, the general and specific hypotheses were affirmed with the Spearman test. And with the information gathered, a proposal was carried out whose theme was the Plan for tourist facilities for the community of La Moya. Then tourist plant was identified, knowledge was strengthened through definitions of the main tourist facilities required in the La Moya community, and the tourist facilities were technically described.